Pan-Cancer Analyses Reveal Oncogenic and Immunological Role of PLOD2 - Xu, Qiqi; Kong, Na; Zhao, Yiguo; Wu, Quan; Wang, Xin; Xun, Xiaodong; Gao, Pengji (Frontiers in Genetics, 2022)
Some previous studies have shown that PLOD2 has some value in tumorigenesis. However, the broad significance of PLOD2 has not been discussed in depth. This study was aimed at elaborated and summarized the value of PLOD2 in various tumors. First, we integrated GTEx, The Cancer Genome Atlas and Cancer Cell Line Encyclopedia databases to analyze the expression of PLOD2, and found that it was expressed differently in normal tissues and significantly highly expressed in most tumors compared with normal tissues. Second, our analysis revealed that PLOD2 expression was negatively correlated with the prognosis of several tumors. For gastric cancer, the median overall survival time was significantly higher in the PLOD2 low expression group [HR 0.616 (95%CI 0.442–0.858), p = 0.004]. Third, for tumor immunity, PLOD2 was significantly associated with tumor infiltration, including immune infiltrating cells; immune checkpoint expression; immune microenvironment scores (immune score, stromal score and estimate scores); immunotherapy-related scores (tumor mutational burden, microsatellite instability, tumor neoantigen burden); expression of DNA repair genes Mismatch Repairs and methyltransferase; and enrichment analyses identified PLOD2-associated terms and pathways. Lastly, twenty pairs of gastric cancer and adjacent immunohistochemistry showed that PLOD2 was significantly overexpressed in gastric cancer (p < 0.001). Collectively, PLOD2 played a significant role in tumorigenesis and maybe serve as a potential biomarker for diagnosis and prognosis in cancers.